(untitled) (Indian Journal of Arid Horticulture, 2025)
The extent of genetic variability, heritability, genetic advance and correlations in respect of eight economic characters in 30 genotypes of brinjal were studied under hot arid environment. The phenotypic and genotypic coefficients of variation were high for number of fruits and fruit yield per plant and fruit weight. High heritability estimates along with high genetic advance for number of fruits and fruit yield per plant and fruit weight indicated the role of additive gene action. Correlation studies revealed that fruit yield per plant was significantly and positively associated with number offruits per plant and fruit weight. The genotypeAHB 02, KSB 73, KSB 33, KSB 39 and F2 (AHB 04 x PPC)showed high mean performance for fruit yield per plant along with earliness trait which can be furthcrtested for direct use as variety or may be c,.sed in breeding programme for improving fruit yield.